Calculation of overall equipment effectiveness weight by Taguchi method with simulation - Yuniawan, Dani; Teruaki, Ito; Mohamad, Effendi (SAGE, 2013)
Overall equipment effectiveness is a comprehensive performance measurement that is used to measure equipment effectiveness on the production line. Overall equipment effectiveness is a key performance indicator to measure the implementation of total productive maintenance. Nevertheless, as the time passes, the usage of overall equipment effectiveness is transformed to a system that analyses production data, to identify potential areas of improvement and support lean initiatives. Therefore, overall equipment effectiveness characteristically advances from being a base measure of efficiency as its initial purpose, to being a tool that improves effectiveness. Even though overall equipment effectiveness appears to be a complete performance measurement indicator, it still requires proper modification. Many researches related to overall equipment effectiveness improvement have used weighted overall equipment effectiveness to advance this performance measurement for production line use. Until now, only a few researches have been conducted by other researchers related to overall equipment effectiveness improvement. Several overall equipment effectiveness improvements have included the cost variable into the overall equipment effectiveness calculation; others have attempted to develop a new technique to set up the weights of overall equipment effectiveness. Since several researches of overall equipment effectiveness improvement have met with difficulty when determining the proper weight for each overall equipment effectiveness element, this research proposes a new procedure to cover this drawback. The baseline for weighting overall equipment effectiveness elements in this research refers to overall equipment effectiveness element characteristics that are obtained by a combined result of simulation and experiment, through the Taguchi method. The research outcome proves that this combination of methods gives a more accurate result for providing characteristic data of a production line related to overall equipment effectiveness and for obtaining a weight calculation of overall equipment effectiveness elements.